2022
DOI: 10.1021/acsami.2c05221
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Activation over Nanoshaped CeO2 Decorated with Nickel for Low-Temperature Methane Dry Reforming

Abstract: Dry reforming of methane (DRM) is a promising way to convert methane and carbon dioxide into H 2 and CO (syngas). CeO 2 nanorods, nanocubes, and nanospheres were decorated with 1−4 wt % Ni. The materials were structurally characterized using TEM and in situ XANES/EXAFS. The CO 2 activation was analyzed by DFT and temperature-programmed techniques combined with MS-DRIFTS. Synthesized CeO 2 morphologies expose {111} and {100} terminating facets, varying the strength of the CO 2 interaction and redox properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Tian et al reported that Ca–Ni interfaces in the CaO–Ni material favored CH 4 dissociation and achieved 65% of CO 2 conversion at 800 °C; Hu et al incorporated thermally stable CeO 2 to CaO–Ni materials, resulting in 90% of CO 2 conversion at a relatively low temperature (650 °C); Kim et al used MgO–Al 2 O 3 as a support material to prepare CaO–Ni@MgO–Al 2 O 3 , where 99.9% of CO 2 conversion was achieved at 720 °C . Overall, the incorporation of catalyst promoters (e.g., ceria) has been shown to improve the activity and stability of the Ni-based catalyst. ,,,, The Ca–Ce and Ca–Ni–Ce interfaces provide alternative catalytic pathways to enhance carbonation and DRM, respectively, instead of using CaO and Ni alone. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al reported that Ca–Ni interfaces in the CaO–Ni material favored CH 4 dissociation and achieved 65% of CO 2 conversion at 800 °C; Hu et al incorporated thermally stable CeO 2 to CaO–Ni materials, resulting in 90% of CO 2 conversion at a relatively low temperature (650 °C); Kim et al used MgO–Al 2 O 3 as a support material to prepare CaO–Ni@MgO–Al 2 O 3 , where 99.9% of CO 2 conversion was achieved at 720 °C . Overall, the incorporation of catalyst promoters (e.g., ceria) has been shown to improve the activity and stability of the Ni-based catalyst. ,,,, The Ca–Ce and Ca–Ni–Ce interfaces provide alternative catalytic pathways to enhance carbonation and DRM, respectively, instead of using CaO and Ni alone. , …”
Section: Introductionmentioning
confidence: 99%
“…9 Overall, the incorporation of catalyst promoters (e.g., ceria) has been shown to improve the activity and stability of the Ni-based catalyst. 4,13,19,24,28 The Ca−Ce and Ca−Ni−Ce interfaces provide alternative catalytic pathways to enhance carbonation and DRM, respectively, instead of using CaO and Ni alone. 1,9 However, the present DFM prepared by the conventional approach (e.g., using a sol−gel-based coprecipitation method) possessed several drawbacks that limited the effectiveness of CO 2 conversion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For different molecules, there may also be a corresponding correlation in the medium temperature range, and its slope value is different from that of Campbell–Sellers correlation. In the application fields of linear correlation, such as heterogeneous catalysis, the temperature usually exceeds 400 K which means it is in the medium temperature range. , In this case, it may be more appropriate to use this linear correlation in the medium temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…[12] Furthermore, catalysts have also been used to combine with plasma, aiming to improve conversion, selectivity, and energy efficiency. [3,[13][14][15] Meanwhile, the various experimental conditions, such as discharge power, [16] gas flow rate, [5] pressure, [17] and CH 4 /CO 2 molar ratio [8] (for simplification, CH 4 /CO 2 is used to stand for CH 4 /CO 2 molar ratio in the following sections), have been extensively investigated in above plasma types. The previous efforts have made significant improvements in raising the reactant conversion and energy efficiency of plasma reforming to be close to that in industrial thermo-catalysis.…”
Section: Introductionmentioning
confidence: 99%